2021
DOI: 10.1108/mf-04-2020-0189
|View full text |Cite
|
Sign up to set email alerts
|

The inter-relationships among liquidity creation, bank capital and credit risk: evidence from emerging Asia–Pacific economies

Abstract: PurposeThis study investigates the inter-relationships among liquidity creation, bank capital and credit risk in selected emerging economies between 2012 and 2016.Design/methodology/approachA three-step procedure as proposed by Berger and Bouwman (2009) is used to measure liquidity creation. Thereafter, a simultaneous equations model with the generalized method of moments (GMM) estimator is used to examine the links between liquidity creation, bank capital and credit risk.FindingsThe findings indicate that ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
3
13
1
Order By: Relevance
“…Following Le and Pham (2021), Le (2020a) and among others, the pairwise Granger causality tests are performed to illustrate the possible two-way relationship between our main dependent variables ( RISK and MKTDIS ). The following pairwise Granger causality model is formed: …”
Section: Methodsmentioning
confidence: 99%
“…Following Le and Pham (2021), Le (2020a) and among others, the pairwise Granger causality tests are performed to illustrate the possible two-way relationship between our main dependent variables ( RISK and MKTDIS ). The following pairwise Granger causality model is formed: …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the profitable ability is crucial in associating the market power and liquidity creation of banks. Previous studies also demonstrated a variation in the liquidity-profitability between large and small banks, as well as high-capitalized and low-capitalized banks (Berger and Bouwman, 2009;Tran et al, 2016;Le and Pham, 2021). For this study, we outline the second hypothesis, to test the role of profitability in the relationship between market power and liquidity creation, as follows:…”
Section: Hypothesis Developmentmentioning
confidence: 98%
“…Moreover, the coefficients of INF are negative and significant, suggesting that inflation rate impacts bank stability negatively. A higher inflation rate would impact borrowers' budgets, which, in turn, limits their liquidity and their capability to service debts (Le and Pham, 2021). This, therefore, may hamper bank stability.…”
Section: The Results Of Our Baseline Modelmentioning
confidence: 99%